"Não admitindo escusa alguma" : confiscos e recrutamentos na guerra civil rio-grandense (1835-1845) - Schmitt, Ânderson Marcelo (2014)
This dissertation analyses the characteristics from the Farroupilha Army on the civil war of 1835-1845, that took place in the province of São Pedro do Rio Grande do Sul. During almost ten years had been in opposite sides rio-grandenses themselves and also the troops sent from other regions of the Empire to fight the rebels. Its main causes were economical and political claim from part of rio-grandense landowner order, which considered themselves damaged by the economical and political organization of the Empire. Looking for identifying the ways in which the rebel forces had to keep war against the Brazilian Empire, in a limited land. From those ways they ought to get the resources and accomplish their fighting tactics and recruiting soldiers for their front-lines. Farroupilhas, understanding the necessity of organizing the withdrawal of resources from farms on the countryside and on the sierra, started to order and coordinate their job, using them as indispensable place of troop supply. Created the fighting existence conditions by farroupilhas, these were complementary to front-line soldiers engagement. The Rebel Army was made of regimentation that took place from part of district and municipal authorities and also of recruiting from officers of Farroupilha Army. Trying to understand why without occurring of some practices, the Rebel Army would not have kept on guns against the Brazilian Empire, which received economical and soldier assistance from other Brazilian provinces. As research source, documentation contemporary to the conflict has been used, such as the farroupilha periodicals, which rounded the sites temporarily subdued by the rebel troops, and the Coleção Varela, which has a wide range of several kinds of documents of civil and military authorities, that informs the relations that could pervade the arrangement the farroupilha political head tried to give their organization